2020
DOI: 10.7150/thno.44556
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of circulating tumor cells of metastatic castration-resistant Prostate Cancer Patients receiving 177Lu-PSMA-617 Radioligand Therapy

Abstract: Rationale: Lu-177-PSMA-617 radioligand therapy (RLT) is currently under approval for treatment of metastatic castration resistant prostate cancer (mCRPC) patients with late stage disease. However, previous studies demonstrated both heterogeneity of prostate specific membrane antigen (PSMA) expression, as well as response to PSMA treatment among mCRPC patients. Thus, there is an unmet need for identifying predictive parametres prior or under PSMA-RLT treatment. We therefore aimed to correlate several… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Our results have shown that PSMA expression in EpCAM-positive CTCs, was significantly correlated with lower OS. However, in a recent study Kessel et al have shown that PSMA expression does not display strong prognostic ability [ 28 ]. This could be due to different isolation and detection methods of CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results have shown that PSMA expression in EpCAM-positive CTCs, was significantly correlated with lower OS. However, in a recent study Kessel et al have shown that PSMA expression does not display strong prognostic ability [ 28 ]. This could be due to different isolation and detection methods of CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, 177 Lu-PSMA-617 radioligand therapy [ 96 ] is expected to soon be approved by the FDA as a treatment for mCRPC, considering the positive results of phase III VISION trial (NCT03511664). Kessel et al evaluated the copy number of CTC AR-V7 mRNA prior to 177 Lu-PSMA-617 administration [ 53 ]. Although the number is small, PSA decline was observed in both AR-V7 negative and positive groups (88% vs. 81%), and there was no statistical difference in PFS and OS between two groups [ 53 ].…”
Section: Ar-vs As Therapeutic Targetsmentioning
confidence: 99%
“…Kessel et al evaluated the copy number of CTC AR-V7 mRNA prior to 177 Lu-PSMA-617 administration [ 53 ]. Although the number is small, PSA decline was observed in both AR-V7 negative and positive groups (88% vs. 81%), and there was no statistical difference in PFS and OS between two groups [ 53 ]. If this result is validated in larger cohorts, then 177 Lu-PSMA-617 may be another primary treatment option for AR-V7 positive mCRPC in addition to taxanes.…”
Section: Ar-vs As Therapeutic Targetsmentioning
confidence: 99%
“…Additionally, PSMA transcript level is overall a surrogate indicator of poor response to currently approved treatments for mCRPC, including enzalutamide, abiraterone, docetaxel, and cabazitaxel [ 52 ]. This is not necessarily the case for patients treated with 177 Lu-PSMA-617 RLT, according to a small cohort of 19 men with mCRPC [ 53 ]. Although PSMA mRNA expression in CTCs correlated with baseline serum PSA and with the MTV on PSMA PET/CT, there was no association with PFS or OS following treatment with 177 Lu-PSMA-617 [ 53 ].…”
Section: Molecular Biomarkersmentioning
confidence: 99%
“…This is not necessarily the case for patients treated with 177 Lu-PSMA-617 RLT, according to a small cohort of 19 men with mCRPC [ 53 ]. Although PSMA mRNA expression in CTCs correlated with baseline serum PSA and with the MTV on PSMA PET/CT, there was no association with PFS or OS following treatment with 177 Lu-PSMA-617 [ 53 ].…”
Section: Molecular Biomarkersmentioning
confidence: 99%